Acidic nuclear phosphoprotein 32kDa (ANP32)B-deficient mouse reveals a hierarchy of ANP32 importance in mammalian development - Reilly, Patrick T. (National Academy of Sciences, 2011)
The highly conserved ANP32 proteins are proposed to function in a broad array of physiological activities through molecular mechanisms as diverse as phosphatase inhibition, chromatin regulation, caspase activation, and intracellular transport. On the basis of previous analyses of mice bearing targeted mutations of Anp32a or Anp32e, there has been speculation that all ANP32 proteins play redundant roles and are dispensable for normal development. However, more recent work has suggested that ANP32B may in fact have functions that are not shared by other ANP32 family members. Here we report that ANP32B expression is associated with a poor prognosis in human breast cancer, consistent with the increased levels of Anp32b mRNA present in proliferating wild-type (WT) murine embryonic fibroblasts and stimulated WT B and T lymphocytes. Moreover, we show that, contrary to previous assumptions, Anp32b is very important for murine embryogenesis. In a mixed genetic background, ANP32B-deficient mice displayed a partially penetrant perinatal lethality that became fully penetrant in a pure C57BL/6 background. Surviving ANP32B-deficient mice showed reduced viability due to variable defects in various organ systems. Study of compound mutants lacking ANP32A, ANP32B, and/or ANP32E revealed previously hidden roles for ANP32A in mouse development that became apparent only in the complete absence of ANP32B. Our data demonstrate a hierarchy of importance for the mammalian Anp32 genes, with Anp32b being the most critical for normal development.